Neutron activation analysis at the Peruvian Institute of Nuclear Energy - Bedregal, Patricia (2003)
A description of facilities, analytical procedures and present applications, for the use of neutron activation analysis technique at the Peruvian Institute of Nuclear Energy is provided, future applications of the technique are also presented.